AN EFFORT TO INCREASE INTEREST IN MATHEMATICAL LEARNING BY USING DISCOVERY LEARNING MODELS ON STUDENTS CLASS VIII - Siti Aisyah; Widayati Widayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
This research was conducted because the problem encountered at State Junior High School 3 (SMP N 3) Prambanan Sleman was the low interest in students' learning mathematics, as seen from the Middle Semester Deuteronomy results. This problem involves students who pay less attention to the learning process and students' feelings towards monotonous learning. Thus, this study aims to increase students' interest in learning mathematics using the discovery learning model. This type of research is Classroom Action Research (CAR). The research setting used in this study was the classroom setting in mathematics learning activities carried out in class VIII B in the second semester of SMP N 3 Prambanan Sleman in the 2018/2019 academic year. Data collection techniques used in this study were observation, questionnaires, and interviews. Analysis of the data used in the analysis of observational data, analysis of student questionnaire response data, and student and teacher interviews analysis. The results of this study indicate that 1) students' interest in learning increases from cycle I to cycle II with the average value of the results of the questionnaire cycle I was 66.08 increased to 70.11 in cycle II; 2) the increase in participation in learning the first cycle was 56.25% increased to 72.92% in the second cycle; 3) the results of the interviews seen more and more students increased interest in learning mathematics. Hoping that using the learning discovery learning model will increase students' interest inÂ  Â learning mathematics.